2017
DOI: 10.1515/ijnes-2016-0026
|View full text |Cite
|
Sign up to set email alerts
|

Contested Practice: Political Activism in Nursing and Implications for Nursing Education

Abstract: Canadian nurses have a social mandate to address health inequities for the populations they serve, as well as to speak out on professional and broader social issues. Although Canadian nursing education supports the role of nurses as advocates for social justice and leadership for health care reform, little is known about how nurse educators understand activism and how this translates in the classroom. A comparative life history study using purposeful sampling and a critical feminist lens was undertaken to expl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(56 citation statements)
references
References 41 publications
0
54
0
2
Order By: Relevance
“…However, to date nurses have not committed to this in great numbers 70 and educators are ambivalent or unsure how to go about supporting students' development in this context. 71 There are many examples related to pediatric pain management affected by injustice, inequality, political and policy decisions and human rights. Nurses' voice in this context could, and many argue should, be influential.…”
Section: This Way Of Knowing Originated From the Development Of A Nurmentioning
confidence: 99%
“…However, to date nurses have not committed to this in great numbers 70 and educators are ambivalent or unsure how to go about supporting students' development in this context. 71 There are many examples related to pediatric pain management affected by injustice, inequality, political and policy decisions and human rights. Nurses' voice in this context could, and many argue should, be influential.…”
Section: This Way Of Knowing Originated From the Development Of A Nurmentioning
confidence: 99%
“…This challenge is achievable if nurses can exhibit negotiable skills, heightened by personal attributes such as persistence, fortitude, willpower, and resilience. Unfortunately, in separates studies, Buck-McFadyen and colleagues, and MacLellan et al have reported the lack of negotiable skills among nurses which generally laid nurses back in political discourse [60,61]. This could be due to the approach of training given to nurses in the Ghanaian context which predisposes them to timidity and unassertiveness.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, I choose Anabasis not only for its aesthetic or literary character (“Xenophon's Anabasis seems today to be regarded universally as his most beautiful book,” Strauss, 1986) but also because it is the work in which the author shows with greater clarity his choice of political affairs, of a practical life. Though young nursing students are maybe not sure about the political character of the nursing profession, they can soon learn how socio‐political constraints have a great influence on their nursing work (Buck‐McFadyen & MacDonnell, 2017).…”
Section: Xenophon’s Anabasismentioning
confidence: 99%